Professional profile of the Certified Public Accountant and his influence on the detection of the acts of corruption in the Moquegua region - Arohuanca Antahuanaco, Bethy Verlina (2021)
The objective of the study was to determine whether the professional profile of the certified public accountant influences the detection of acts of corruption in the Moquegua region. Considering that, nowadays, the Moquegua region is one of the regions with more cases of corruption nationwide. In this regard, the State and private companies have adopted measures, they do not consider the professional accountant to counteract corruption. In order to achieve the proposed objective, the study was placed as a basic research of descriptive and explanatory level, not experimental and transversal, using the logistic regression model Logit was used, where the dependent variable is dichotomous and the independent variables are in an interval scale. As a result, it was determined that the professional profile of the certified public accountant, that has professional experience of six to ten years, specializing in General Accountant, specialist in Finance, Tax, International Financial Reporting Standards, Costs, Budgets, Accounting Integrator and Auditor, with constant training from 501 to more hours in the last five years and who is in the age range of 31 to 45 years, significantly influences the detection of acts of corruption in the Moquegua region.